LITERATURE REVIEW BAYI BERAT LAHIR RENDAH - Upus Piatun Khodijah (Jurnal Kebidanan Besurek, 2023)
Indonesia is one of the developing countries with the highest maternal mortality and infant. The infant mortality cases in 2015 as many as 33,278 cases decreased compared to the year 2015 of 32,007 and in 2017 in the first semester as many as 10,294 cases. One of the causes is the incidence of Low Birth Weight (LBW) of 38.85%. LBW is the birth weight less than 2,500 grams. The review of LBW is done by literature review from DOAJ, Pubmed, Scholar and Garuda portal. The literature search using several keywords is "Low Birth Weight ", "risk factors" with four literature publications from 2007-2017. LBW incidence is influenced from maternal demography status, maternal health status, condition of pregnancy and baby. The four journals DOAJ, Pubmed, Scholar and Garuda portal described risk factors of LBW occurrence include sociodemography (maternal age <18 years and> 34 years, education level, occupation type, family income, kin), maternal health status obstetric history, parity, birth spacing, anemia, history of diabetes, malaria, baby malpresentation history, Premature Rupture Of The Membrane, maternal nutritional status, infections, diseases and complications of pregnancy), status of ANC (frequency and quality of care, health worker, site of pregnancy examination, history of unchecked pregnancy, irregular ANC).